The Vale de Abrutiga uranium phosphates mine, central Portugal - Pinto, Marina M. S. Cabral (2007)
A brief summary about the composition and origins of the U deposit is present. The mineralization is composed by secondary uranium phosphates (saleeite and meta-saleeite). The precipitation was probably the main responsible factor for U retention within the quartz veins leading to the uranium phosphate mineralization of Vale de Abrutiga.